Bending Stress and Deformation Characteristics of Gas Pipelines in Mountainous Terrain Under the Influence of Subsidence - Guozhen Zhao; Jiadong Li; Haoyan Liang (Energies)
Aiming at the problem that the surface subsidence caused by coal mining in mountainous areas will pose a potential threat to the safe operation of gas pipelines in goaf subsidence areas, taking the geological conditions of Mugua Coal Mine in Shanxi Province as the research background, through the combination of similar simulation and finite element simulation, the deformation and stress characteristics of gas pipelines affected by subsidence in mountainous terrain are analyzed, and the failure law of gas pipelines in different terrains of the coal mining area is revealed. The results demonstrate that topographic stress convergence creates a maximum compression zone at the valley base of the central subsidence basin, causing significant pipeline depression. Hillslope areas primarily experience tension from soil slippage, while slope–valley transition zones exhibit a high-risk shear–tension coupling. Analysis via the pipe–soil interaction model reveals concentrated mid-subsidence pipeline stresses with subsequent relaxation through redistribution. Accordingly, the following zoned protection strategy is proposed: enhanced compression monitoring in valley segments, tensile reinforcement for slope sections, and prioritized shear prevention in transition zones. The research provides a theoretical basis for the safe operation and maintenance of gas pipeline networks in mountainous areas.